Amplifying the benefits of agroecology by using the right cultivars - Noguera, D; Laossi, KR; Lavelle, Patrick M.; Cruz de Carvalho, M.H.; Asakawa, N.; Botero, César; Barot, Sébastien (Wiley, 2011)
Tropical soils are particularly vulnerable to fertility losses due to their low capacity to retain organic matter and mineral nutrients. This urges the development of new agricultural practices to manage mineral nutrients and organic matter in a more sustainable way while relying less on fertilizer inputs. Two methods pertaining to ecological engineering and agroecology have been tested with some success: (1) the addition of biochar to the soil, and (2) the maintenance of higher earthworm densities. However, modern crop varieties have been selected to be adapted to agricultural practices and to the soil conditions they lead to and common cultivars might not be adapted to new practices. Using rice as a model plant, we compared the responsiveness to biochar and earthworms of five rice cultivars with contrasted selection histories. These cultivars had contrasted responsivenesses to earthworms, biochar, and the combination of both. The mean relative increase in grain biomass, among all treatments and cultivars, was 94% and 32%, respectively, with and without fertilization. Choosing the best combination of cultivar and treatment led to a more than fourfold increase in this mean benefit (a 437% and a 353% relative increase in grain biomass, respectively, with and without fertilization). Besides, the more rustic cultivar, a local landrace adapted to diverse and difficult conditions, responded the best to earthworms in terms of total biomass, while a modern common cultivar responded the best in term of grain biomass. This suggests that cultivars could be selected to amplify the benefit of biochar- and earthworm-based practices. Overall, selecting new cultivars interacting more closely with soil organisms and soil heterogeneity could increase agriculture sustainability, fostering the positive feedback loop between soils and plants that has evolved in natural ecosystems.